Improving the Quality of Etawa Milk Products Through Packaging Updates, Product Logos and Halal Certification Registration - Ardita Arum Meilana; Ali Hafidz Bachtiar; Ikke Furi Rahayu; Wiranti Wiranti; Gabriel Muhammad Farih; Khoirurrosyidin Khoirurrosyidin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Etawa milk is a processed product that has high nutritional value and is popular with Indonesian people. This activity aims to update the packaging so that it can increase the attractiveness of the product so that the product is more easily recognized on the market. The methods used in the form of training and mentoring, packaging updates that display clear information about the product, nutritional benefits, and consumption methods can increase consumer perceptions of the quality of